Optical studies of self-assembled InGaAs/GaAs quantum dot structures drown by atomic layer epitaxy - Rho, H; Song, JD; Park, YJ; Choi, WJ; Lee, JI (KOREAN PHYSICAL SOC, 2004)
We report photoluminescence (PL) and Raman scattering studies of self-assembled InGaAs/GaAs quantum dot (QD) structures grown by atomic layer epitaxy (ALE). PL spectra show that the ground-state energies of the InGaAs QDs decrease with increasing deposition periods from n = 3 to 7. Correspondingly, with increasing, n, Raman spectra show that the longitudinal optical (LO) phonon energies (similar to 291 cm(-1)) of GaAs decrease, indicating that tensile strain is induced in the GaAs matrix. The PL and the Banian results strongly suggest that the QDs grow in size with increasing deposition periods, giving rise to reduction of the quantum confinement effect and relaxation of strain. Importantly, a spectral response at similar to 237 cm(-1) was observed in Raman scattering. This Raman response is attributed to the InAs-like LO phonon mode of the InGaAs QDs, indicating clear evidence of the formation of the ALE-grown QDs.
Keywords: TEMPERATURE-DEPENDENCE; PHOTOLUMINESCENCE; GROWTH; SIZE